Pemberian Video Edukasi terhadap Pengetahuan tentang Pendewasaan Usia Perkawinan (PUP) pada Remaja - Zuhairi Lubis; Yora Nopriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of video in increasing knowledge about maturing marriage age in young SMK Bakti Ibu 3 Palembang students. This research method uses a pre-experimental design with a pre-post-test design with a control group. The results showed that 18 respondents (45%) had a low level of knowledge, 20 respondents (50%) had a sufficient level of expertise, and 2 respondents (5%) had a good level of understanding. The analysis results using the t-test were obtained (p-value 0.000). In conclusion, providing educational videos can increase respondents' knowledge about maturing at the age of marriage. Keywords: Knowledge, Marriage, Youth, Video